On the Design of a Continous-Time Channel Select Filter for a Zero-IF UMTS Receiver - Maurer, Linus; Schelmbauer, Werner; Pretl, Harald; Adler, Bernd; Springer, Andreas; Weigel, Robert (51st Vehicular Technology Conference, 2000)
This paper presents the design-flow of a channel select filter for a zero-IF receiver suitable for the Universal Mobile Telecommunications System (UMTS) frequency division duplex (FDD) mode. The necessary filter behaviour is determined from system specifications. These results are used as input for the design of the filter on circuit level. A system overview of the UMTS terrestrial radio access (UTRA) physical layer is presented and the advantages and shortcomings of the zero-IF receiver structure are addressed
elib2cris::1512001600,maurer2000a
Keywords: Receivers; Physical layer; Mobile communication; Information filters; Information filtering; Downlink; Design engineering; Cellular phones; Baseband; 3G mobile communication